Metastatic plasma cell leukemia to the skin: a case report with review of the literature - Elena Pezzolo; Deborah Saraggi; Luigi Naldi (PAGEPress Publications, 2021)
Plasma cell leukemia (PCL) is a rare variant of leukemia with an aggressive clinical course and a poor prognosis. The cutaneous involvement in PCL is very rare either at clinical presentation of leukemia, namely "leukemia cutis", or in the metastatic PCL to the skin. We present a case of eruptive multiple cutaneous nodules in a 56-year-old man with metastatic PCL. Histologically, a diffuse dermal and subcutaneous infiltration of ovoid cells with amphophilic cytoplasm and eccentrically located nucleus consistent with plasmacytoid morphology was observed. Neoplastic cells showed strong immunoexpression for CD138 and CD38 consistent with plasma cells phenotype, and loss of expression of CD56. Kappa light chain restriction similar to the phenotype of his PCL was demonstrated. We suggest that the evaluation of new skin lesions in leukemic patients should include a histopathologic examination to establish the diagnosis as soon as possible and a correct management of the disease.